Impulse Buying Generasi Z: Peran Mediasi Pay Later Pada Hedonisme Dan Framing Diskon - Affandy, Nur Rahmawati; Usamah, Usamah (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
The rapid development of internet technology and digital financial services has led to the emergence of impulse buying behaviour among Generation Z. One of the main drivers is hedonic motivation, promotional strategies in the form of price discount framing and easy access to pay later as a payment method. This study aims to examine the role of using Pay Later as a mediating variable in the relationship between Hedonic Motivation and Price Discount Framing with Impulse Buying in Generation Z in Pekalongan. This quantitative research was conducted in Pekalongan with 259 respondents of Generation Z pay later users who were taken using purposive sampling method. This research was analysed using PLS SEM with the help of SmartPLS 4.0 software. The data analysis method in this study uses model measurement evaluation through the outer model and inner model. The results showed that Hedonic Motivation has a positive and significant effect on Impulse Buying, Price Discount Framing has a positive and significant effect on Impulse Buying, Use of Pay Later has a positive and significant effect on Impulse Buying, The use of Pay Later does not mediate the influence of Hedonic Motivation on Impulse Buying, but the use of Pay Later mediates the influence of Price Discount Framing on Impulse Buying. These findings indicate that the use of Pay Later not only strengthens the influence of Price Discount Framing on impulse buying through its mediating role, but also directly contributes to an increase in impulse buying, even though it is unable to mediate the relationship between Hedonic Motivation and this behavior.